2021
DOI: 10.1108/dprg-04-2021-0055
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of local government revenue collection information system success in Tanzania

Abstract: Purpose This study aims to adapt the updated DeLone and McLean model to evaluate the success of the local government revenue collection and information system (IS) implemented in Tanzania. Design/methodology/approach The study used a concurrent mixed research design integrating quantitative and qualitative data within a single investigation. A total of 296 users from local government authorities (LGAs) in 5 regions in Tanzania participated in the study. Findings The study found that the system quality and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Rating is a process by which land is taxed and the valuation for rating Act 3 authorizes the City Council authorities to value land for the determinations of daunting charges. City Council authorities have power to license some activities and business within their area (Bickelhaupt & Houk, 2017;Sausi et al, 2021;Ulfa, 2018). Therefore, they introduce some costs for issuance of such authorization.…”
Section: Rates and Borrowingmentioning
confidence: 99%
See 1 more Smart Citation
“…Rating is a process by which land is taxed and the valuation for rating Act 3 authorizes the City Council authorities to value land for the determinations of daunting charges. City Council authorities have power to license some activities and business within their area (Bickelhaupt & Houk, 2017;Sausi et al, 2021;Ulfa, 2018). Therefore, they introduce some costs for issuance of such authorization.…”
Section: Rates and Borrowingmentioning
confidence: 99%
“…Concerning City Council authorities, these have statutory borrowing power through a majority support by its members present in the meeting (Sausi et al, 2021;Sbragia, 2019). A City Council authority can increase money through loans for the resolution of its purposes.…”
Section: Rates and Borrowingmentioning
confidence: 99%
“…It has been indicated that facilitation conditions have a significant predictive prowess on users’ behavioral adoption of m-government (Thao, 2017). Whilst studies have shown that facilitating conditions had no positive impact on the adoption of m-government service (Sausi et al, 2021), other research revealed contradictory outcomes that have demonstrated that facilitation conditions have a significant effect on the behavioral adoption of technology (Sim et al, 2018; Mandari and Chong, 2018). With this, we can therefore surmise and propose H2.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In Tanzania, initiatives have been taken by LGAs since the 1990s to establish GITS and integrate it into their functions to enhance revenue collection and implement spatial technologies (Mzava et al, 2019;Namangaya, 2018;Worrall et al, 2017;Mtalo, 2016;World Bank, 2015). Since 2006, numerous GITSs have been obtained and installed in LGAs in Tanzania, with the assistance of the World Bank, TSCP, and PO-RALG (Sausi et al, 2021;Kessy, 2019;McCluskey & Huang, 2019;McCluskey et al, 2018;Pérez-Mira et al, 2017) to support decision-making, policy, and planning. Nevertheless, despite significant investments made in GITSs by the Tanzania government, the majority of LGAs in the country only met roughly between 40%-70% of their collection goals (CAG, 2020).…”
Section: Introduction 11 Background Of the Studymentioning
confidence: 99%